2012
DOI: 10.1167/iovs.12-10308
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Function and Morphology in Monkeys with Ethambutol-Induced Optic Neuropathy

Abstract: The attenuated PhNR and histopathology of the retina indicated that RGCs were markedly damaged, both functionally and morphologically in monkeys with ethambutol-induced optic neuropathy. These results implied that RGCs are predominantly affected in the retina of patients with ethambutol-induced optic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
(49 reference statements)
3
17
0
Order By: Relevance
“…Ganglion cell toxicity has been proposed as a pathophysiologic mechanism in these optic neuropathies, although the precise mechanism remains poorly understood (2)(3)(4)(5). Ganglion cell toxicity has been proposed as a pathophysiologic mechanism in these optic neuropathies, although the precise mechanism remains poorly understood (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Ganglion cell toxicity has been proposed as a pathophysiologic mechanism in these optic neuropathies, although the precise mechanism remains poorly understood (2)(3)(4)(5). Ganglion cell toxicity has been proposed as a pathophysiologic mechanism in these optic neuropathies, although the precise mechanism remains poorly understood (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…This is similar with earlier studies in animals, that found decreased retinal ganglion cell density among animals fed by ethambutol. 11,12 However, the reduction is still in the standard deviation range, and is still less than the value considered significant set at the beginning of the study (10 μm). Recalculation of samples size revealed that the power was less than 80%, so the sample size of this study is considered insufficient.…”
mentioning
confidence: 73%
“…3 Various studies performed in animal have shown decreased amount of retinal ganglion cells in animals treated with ethambutol. 11,12 So that nowadays retinal ganglion cell damage is more widely believed to cause EON.…”
Section: 4mentioning
confidence: 99%
“…The third patient had a different impairment of visual pathways situated in the central nervous system beyond the chiasma and could involve optic tracts, optic radiations or the striate visual areas. The impact of EMB on the optic tracts has been pointed out by some authors; 19 however, the mechanism of toxicity is most likely different from that of RON.…”
Section: Discussionmentioning
confidence: 98%